The role of the library in supporting ICT learning in primary school - Nayla Muthi Ainan (Hipkin Journal of Educational Research, 2025)
In the context of primary education, libraries have great potential as learning resource centers that can support the integration of technology into the learning process. This study examines the role of libraries in supporting Information and Communication Technology (ICT) learning at the Ibnu Sina Integrated Islamic Elementary School (SDIT). The purpose of this study was to examine the extent to which libraries contribute to ICT learning and to identify challenges associated with the use of digital technology in the school environment. The method was qualitative, with data collected through interviews with school officials, including the vice principal for curriculum, as well as observations and document analysis. The results showed that, despite the availability of a Learning Management System (LMS) and an e-book collection, the library's function remains limited to providing materials. Limited digital skills and infrastructure are the main obstacles. The implemented Kurikulum Merdeka provides flexibility in ICT learning, but still requires adaptation of technology-based content. Therefore, it is recommended that digital training be expanded, digital collections enriched, and infrastructure strengthened to enable libraries to play a more effective role.   Abstrak Pada konteks pendidikan dasar, perpustakaan memiliki potensi besar sebagai pusat sumber belajar yang dapat mendukung integrasi teknologi dalam proses pembelajaran. Penelitian ini mengkaji peran perpustakaan dalam mendukung pembelajaran Teknologi Informasi dan Komunikasi (TIK) di Sekolah Dasar Islam Terpadu (SDIT) Ibnu Sina. Tujuan dari penelitian ini adalah untuk mengeksplorasi sejauh mana perpustakaan berkontribusi dalam pembelajaran TIK, serta mengidentifikasi tantangan yang muncul dalam pemanfaatan teknologi digital di lingkungan sekolah. Metode yang digunakan yaitu kualitatif dengan pengumpulan data melalui wawancara dengan pihak sekolah, termasuk wakil kepala sekolah bidang kurikulum, observasi dan analisis dokumen. Hasil penelitian menunjukkan bahwa meskipun telah tersedia Learning Management System (LMS) dan koleksi e-book, fungsi perpustakaan masih terbatas pada penyediaan materi. Keterbatasan keterampilan digital dan infrastruktur menjadi hambatan utama. Kurikulum Merdeka yang diterapkan memberikan fleksibilitas pembelajaran TIK, namun masih memerlukan penyesuaian konten berbasis teknologi. Oleh karena itu, disarankan adanya peningkatan pelatihan digital, pengayaan koleksi digital, dan penguatan infrastruktur agar perpustakaan dapat berperan lebih optimal. Kata Kunci: Kurikulum Merdeka; literasi digital; pembelajaran TIK; perpustakaan sekolah